Bandung Conference 70 Years On: Visions of Decolonisation for a Multipolar World Order - Umar, Ahmad Rizky M.; Yuana, Suci Lestari; Hakim, Luqman-nul; Mas'oed, Mohtar (Global South Review, 2025)
This special issue aims to reflect on the legacies of the Bandung Conference in its 70th anniversary for the emerging multipolar world order. Seven articles in this special issue unpacks the many legacies of the Bandung Conference: from the epistemic visions of a new international order based on self-determination, sovereign equality, and postcolonial justice to the reshaping of the foreign policy of the ‘global south’ countries. We build on the legacies and pitfalls of the Bandung Conference to rethink what it means by, and what should be done for, the decolonisation agenda in world politics. We argue that the Bandung Conference has been able, primarily, to rethink the structure of international politics by embracing three visions of decolonisation: a political vision of territorial sovereignty and self-determination, an economic vision of equality and justice, and an epistemic vision for cultural and intellectual liberation from colonial legacies. However, these visions of decolonisation are threatened by the return of great power politics, sphere of influence, and the further marginalisation of the global south in an emerging multipolar world order. We argue that the global south needs to use opportunities from the multipolar world order to reassert their voices and agencies while at the same time critical of, and rejecting, the underlying imperial logic of the great powers. This special issue lays out some lessons from the Bandung Conference for a multipolar world order in three key sites of new global struggle: a political struggle to defend sovereignty, an economic struggle for global justice, and an intellectual struggle for equal knowledge production. These are the new Bandung visions for a multipolar world order.